2020
DOI: 10.1177/1012690220912415
|View full text |Cite
|
Sign up to set email alerts
|

National sport success and the emergent social atmosphere: The case of Iceland

Abstract: Iceland attracted international attention when its national football team qualified for the 2018 Men’s World Cup. This surprise qualification made Iceland the smallest nation to qualify in the 88-year history of the prestigious competition. During the World Cup, life in Iceland seemed to center on the Icelandic team and attract interest and attention from almost every Icelander. But how widespread was the national interest in Iceland’s participation and did the inclusion of Iceland in the competition have any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…The words global, world, English, rename, and leave a name attracted a high number of like comments, indicating that users wanted to advertise the CPBL to the world as an expression of their national identity. These findings are different from those of earlier studies [19,20] ascribing national identity to a satisfactory performance of the national team, the participation of Taiwanese players in professional leagues abroad, and the efficient hosting of international sporting events. In the present study, the in-depth exploration of online content revealed that sport fans' (users') national identity was attributed to the country's effective pandemic prevention.…”
Section: Social Identitycontrasting
confidence: 99%
“…The words global, world, English, rename, and leave a name attracted a high number of like comments, indicating that users wanted to advertise the CPBL to the world as an expression of their national identity. These findings are different from those of earlier studies [19,20] ascribing national identity to a satisfactory performance of the national team, the participation of Taiwanese players in professional leagues abroad, and the efficient hosting of international sporting events. In the present study, the in-depth exploration of online content revealed that sport fans' (users') national identity was attributed to the country's effective pandemic prevention.…”
Section: Social Identitycontrasting
confidence: 99%
“…Future research can also look more widely at gatherings of secular groups, which are not intentionally ‘rituals’ but nonetheless may create a sense of connection to something bigger than oneself. A variety of gatherings may function as a form of ‘implicit religion’ [ 85 – 87 ], such as sporting events where one feels connected to a team spirit [ 88 , 89 ], thus creating social bonds in ways similar to religious rituals. Conducting research in such settings would allow us to better understand the nature and effects of ritual-like social bonding in secular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Flags, particularly those representing countries or cultures, have been identified as totems that are imbued with, and representative of, shared group emotion(s) (Collins, 2004 ). Such emblems can induce intense feelings, on individual and collective levels, of pride and connection to a social group (Halldorsson, 2020 ) whilst simultaneously being an immediate symbol of division that can elicit hatred in others (Guibernau, 2013 ; Moeschberger & Phillips, 2014 ). The rainbow flag, the Pride symbol, is no different.…”
Section: Analysis and Discussion Of Themesmentioning
confidence: 99%